Single freeze per vein strategy with the second-generation cryoballoon for atrial fibrillation: a propensity score-matched study between 180- and 240-s application time in a large cohort of patients. Issue Volume 20:Issue FI 3(2018) (2nd November 2017) - De Regibus, Valentina; Abugattas, Juan-Pablo; Iacopino, Saverio; Mugnai, Giacomo; Storti, Cesare; Conte, Giulio; Auricchio, Angelo; Ströker, Erwin; Coutiño, Hugo-Enrique; Takarada, Ken; Salghetti, Francesca; Lusoc, Ian; et al.
Abstract: Aims: The single-freeze strategy using the second-generation cryoballoon (CB-A, Arctic Front Advance, Medtronic, Minneapolis, MN, USA) has been reported to be as effective as the recommended double-freeze approach in several single-centre studies. In this retrospective, international, multicentre study, we compare the 3-min single-freeze strategy with the 4-min single-freeze strategy. Methods and results: Four hundred and thirty-two patients having undergone pulmonary vein isolation (PVI) by means of CB-A using a single-freeze strategy were considered for this analysis. A cohort of patients who were treated with a 3-min strategy (Group 1) was compared with a propensity score-matched cohort of patients who underwent a 4-min strategy (Group 2). Pulmonary vein isolation was successfully achieved in all the veins using the 28-mm CB-A. The procedural and fluoroscopy times were lower in Group 1 (67.8 ± 17 vs. 73.8 ± 26.3, P < 0.05; 14.9 ± 7.8 vs. 24.2 ± 10.6 min, P < 0.05). The most frequent complication was PNP, with no difference between the two groups ( P = 0.67). After a mean follow-up of 13 ± 8 months, taking into consideration a blanking period of 3 months, 85.6% of patients in Group 1 and 87% of patients in Group 2 were free from arrhythmia recurrence at final follow-up ( P = 0.67). Conclusion: There is no difference in acute success, rate of complications, and freedom from atrial fibrillation recurrences during the follow-up between 3-min and 4-min per vein freeze strategies. The procedural and fluoroscopy times were significantly shorter in 3-min per vein strategy.